ANALISIS KONSUMSI RUMAH TANGGA PETANI PADI DAN PALAWIJA DI KABUPATEN DEMAK - Niken Agustin; Hadi Sasana (Diponegoro Journal of Economics, 2012)
Household consumption is expenditure that it is allocated to physical and spiritual needs of life. The average expenditure of resident of Demak Regency is lower than the average expenditure of people of Cenral Java. This low rate consumption has implications on the number of pre-prosperous family. This research aims to analyze the consumption pattern and the factors that affect household consumption of rice and crops farmers in Demak Regency. The analysis of consumption pattern uses descriptive analysis and it is equipped with cross-tabulations of the data respondents while the analysis to determine the factors affect the consumption uses regression analysis. This research used 99 samples of household in eight districts in Demak Regency. The result showed that household consumption of rice and crops farmers is still dominated by food consumption. The average food consumption cost is Rp 9.621.657,00 per year. The factors affect household consumption of rice and crops farmer are income,  family member that live together in one place, and the use of credit. Education variable doesn’t significantly affect household consumption of rice and crops farmer.